Estado nutricional materno y neonatal en un grupo de adolescentes de la ciudad de Medellín (2015)
ABSTRACT: in developing countries, including Colombia, teen pregnancy is a public health problem. It brings social, health and nutritional consequences for the mother/son binomial. Objective: to assess demographic, socioeconomic, food security, health and nutritional status characteristics in a group of pregnant teenagers and their newborns. Methodology: a cross sectional analytical study was performed in 294 pregnant teenagers in their third trimester of pregnancy enrolled in the prenatal care programs of the public network of hospitals in Medellin-Colombia between 2011 and 2012. Association between the mother ́s body mass index, iron nutritional status and newborn ́s weight at birth using explicative variables was assessed. Results: monthly incomes under a minimum salary were associated with low mother ́s weight and newborns small for gestational age. Low gestational weight was higher in pregnant women under 15 years of age and with a gynecological age under five years. The prevalence of anemia was low in the first trimester and increased at the end of pregnancy; 5.6% had adequate iron reserves. Low weight at birth was associated with infections and mother ́s low weight in the third trimester of pregnancy. Conclusion: teenage pregnancy is a complex problem associated with negative effects in the nutritional, health and social status of the girl and their newborn.